Strategi Komunikasi Simbolik dalam Interaksi Pelayanan yang Dilakukan Penyandang Disabilitas di Difel Cafe Gantari Jaya - Kadek Ayu Natalia; Ratna Devy Winayanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study discusses the symbolic communication strategies employed by individuals with disabilities in the context of service delivery at an inclusive café. The phenomenon examined focuses on how individuals with physical or sensory limitations are able to build meaningful interactions through the use of symbols, sign language, facial expressions, and body movements. The aim of this research is to understand the role of symbolic communication in creating equitable, friendly, and inclusive services for society. The method used is a literature study by analyzing various scientific sources related to symbolic communication and the interaction practices of people with disabilities. The results of the study indicate that symbols play a central role in facilitating communication, fostering understanding, and building trust between individuals with disabilities and the wider community. Furthermore, symbolic communication strategies function as a bridge to break down social stigma, highlight the potential of individuals with disabilities, and strengthen the practice of social inclusion. The novelty of this research lies in portraying symbolic communication strategies not only as technical instruments but also as carriers of human values such as empathy, acceptance, and respect for diversity. Thus, this study provides both theoretical and practical contributions to the development of inclusive communication in the realm of public services.